Molecular communication in nanomedicine - Wong, Chan Mun. (2013)
In wireless radio communication, information messages are transmitted by transmitter to receiver via electromagnetic signal. Similarly, in molecular communication, the transmission and reception of information are realized through molecules. For example, to transmit bit 1, a single molecule or a number of them are transmitted by a transmitter at the beginning of the fixed-duration time slots. If the transmitter transmits no molecule within a fixed-duration time slot, then bit 0 is assumed to be transmitted. Molecular communication is a promising communication paradigm for nanonetworks, and important for nanomedicine applications which include therapeutic nanomachines, such as engineered bacteria and nanorobots. For example, a group of bacteria can be genetically engineered to recognize and destroy tumors in the human body.